IPASTE Framework: A Novel Perspective of Conducting Systematic Literature Review of Tourism under the influence of COVID 19: influence of COVID 19 on Tourism - A Dar, Shahnawaz (Turizam, 2021)
The world was discussing over tourism and in between came zero tourism with the movement of people restricted within their usual place of residence. COVID 19 no doubt has severely impacted all the sectors of economy and hence is a point of concern and research for academia as well as industry. The budding curiosity in the impact of COVID 19 on Tourism industry by the researchers increases the need of systematic review of literature on the topic and identification of future research ways in this particular field. The study is being done to investigate the comprehensive research work on influence of COVID 19 on Tourism industry and to answer the pertinent questions in this regard, like, what has been discussed and explored so for, distribution of the selected studies in the indexed Journals, identification of research lines, contribution of these studies in line with these research lines and the most cited studies. For the systematic review 320 research papers were gathered, 100 among them were removed due to various reasons and the remaining 220 were used as data for the analysis of the study. By conducting the systematic review, 8 research lines were identified and the selected studies were analysed in terms of their contribution vis a vis these research lines. The novelty of this study lies in the new framework developed for systematic literature review in the form of IPASTE. The study has done a comprehensive analysis of the literature on the basis of the new framework to reveal the impact of COVID 19 on the tourism industry on the basis of its six components. The study also identifies some key themes on the basis of research focus of the selected studies. The study has wider implications for mangers, researchers and academicians, to deal with the pandemic and to conduct further research.
Keywords: Tourism